2020
DOI: 10.1371/journal.ppat.1008665
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional evaluation of de novo-designed, two-component nanoparticle carriers for HIV Env trimer immunogens

Abstract: Two-component, self-assembling nanoparticles represent a versatile platform for multivalent presentation of viral antigens. Computational design of protein nanoparticles with differing sizes and geometries enables combination with antigens of choice to test novel multimerization concepts in immunization strategies where the goal is to improve the induction and maturation of neutralizing antibody lineages. Here, we describe detailed antigenic, structural, and functional characterization of computationally desig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 93 publications
(191 reference statements)
6
66
2
Order By: Relevance
“…While antibody-induced trimer degradation appears to be a problem for many of the current Env trimers being used for immunogenicity studies, there are versions of the trimer resistant to this phenotype. We recently demonstrated that an advanced version of the ConM SOSIP trimer (ConM SOSIP.664v9) that includes an engineered interprotomer disulfide bond between residues 72 and 564 resists serum-induced degradation that was observed in the parental ConM SOSIP.664v7 ( 21 ). An interprotomer disulfide between residues 501 and 663 of the 16055 Env was also recently reported to prevent native flexibility linked (NFL) trimer degradation induced by bnAbs 3BC315 or 1C2 ( 4 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While antibody-induced trimer degradation appears to be a problem for many of the current Env trimers being used for immunogenicity studies, there are versions of the trimer resistant to this phenotype. We recently demonstrated that an advanced version of the ConM SOSIP trimer (ConM SOSIP.664v9) that includes an engineered interprotomer disulfide bond between residues 72 and 564 resists serum-induced degradation that was observed in the parental ConM SOSIP.664v7 ( 21 ). An interprotomer disulfide between residues 501 and 663 of the 16055 Env was also recently reported to prevent native flexibility linked (NFL) trimer degradation induced by bnAbs 3BC315 or 1C2 ( 4 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Encouragingly, Env trimer constructs that contain interprotomer disulfide bonds that are resistant to antibody-dependent degradation already exist ( 21 ). Additional disulfides may provide further stability, although these will need to be tested in immunogenicity studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative-stain electron microscopy (nsEM) experiments were performed as previously described 27 , 28 . All samples (free trimers or assembled nanoparticles) were diluted to 20–50 µg/mL and loaded onto the carbon-coated Cu grids (400-mesh, glow-discharged at 15 mA for 30 s).…”
Section: Methodsmentioning
confidence: 99%